Boric Acid Solution Inhibits Candida albicans Infections in Mouse Skin via the IL-23/Th17 Axis - Liu, Zhao; Liu, Qing; Xu, Yanyan; Han, Zhao; Zhang, Ling; Li, Xiaojing (Frontiers in Microbiology, 2022)
To study the effect and mechanism of 3% boric acid solution (BAS) against Candida albicans (CA) infection through the interleukin-23 (IL-23)/T helper 17 cell (Th17) axis. Thirty-six female mice were randomly divided into three groups, and two injection sites were randomly selected on the back of the mice. Group N was injected with sterile water for injection (SWFI), and Group M and Group B were injected with CA mycelium suspension. After successful model verification, the remaining mice entered the following treatments five days later. Group B was treated with 3% BAS, Group M was treated with SWFI, and Group N was not treated. Levels of interleukin-17 (IL-17), IL-22, and IL-23 in mouse blood were measured on days 1, 3, 5, and 7 of treatment. On day 7, IL-17, IL-22, and IL-23 in mouse skin were detected. Serum levels of IL-17, IL-22, and IL-23 in Group M were higher than in Group N on the first day of treatment (P < 0.05). Expression levels of IL-17, IL-22, and IL-23 in the epidermis of the skin lesions in Group M were higher than in Group N on day 7 (P < 0.05). The serum level of IL-17 in Group B was higher than in Group M on days 5 and 7 (P < 0.05). Serum levels of IL-22 in Group B on days 1, 5, and 7 were higher than in Group M (P < 0.05). Serum levels of IL-23 in Group B were higher than in Group M on days 3, 5, and 7 (P < 0.05). IL-17 and IL-23 in Group B reached a peak on day 5, significantly different on days 1, 3, and 7 (P < 0.05). The expression intensity of IL-17, IL-22, and IL-23 in the skin lesions of Group B was higher than that of Group M on day 7 (P < 0.05). We conclude that IL-17, IL-22, and IL-23 are involved in the anti-CA activity in mouse skin, and 3% BAS increased IL-17, IL-22, and IL-23 to mediate these effects.